THE SOCIAL CHANGE AND COLLECTIVE BEHAVIOR DEPICTED IN RICHARD LONCRAINE’S 5 FLIGHTS UP - Asti, Yulia (LANTERN (Journal on English Language, Culture and Literature), 2017)
Basically every individual experiences changes in their life. People change, and so do society. In the 5 Flights Up Film, the writer is interested to find the major sources of social change such as the population growth, the infrastructure development, and technological innovation that produces smartphones and the internet. Somehow, technological innovation has influenced the life style, way of living, and behavior of the society in this modern era. The writer is also interested in analyzing the types of collective behavior namely rumor, mass hysteria, and panics among the society regarding a particular issue. In analyzing this film, the writer used library research as the method of research. Objective and sociology of literature approaches are used as the method of approach. As the result, the writer is able to observe what affects Mr. and Mrs. Carver’s decision to cancel selling their house and decide to stay in their five floor apartment. Moreover, the film often represents certain issue and it highlights its perspective on the issue. Thus, the writer also emphasizes that through the film everyone can learn to gain the sense of awareness about particular phenomenon occurred within society.